2022
DOI: 10.1093/sysbio/syac061
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic Evolution of the Skull in Labrid Fishes Involves Differences in Both Tempo and Mode of Morphological Change

Abstract: Abstract.—Modularity is a ubiquitous feature of organismal design that plays an important role in structuring patterns of morphological diversification. Modularity can facilitate evolutionary changes by allowing subsets of traits to coevolve as integrated units and follow quasi-independent evolutionary trajectories, a pattern that may be particularly consequential in the case of highly complex morphological structures. Here we examine modularity in a complex and highly kinetic structure, the teleost skull, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 101 publications
3
21
0
Order By: Relevance
“…These cranio-vertebral and hyo-pectoral interfaces lead to a more efficient suction mechanism and act as anchors to stabilize the head or to transfer power from the body during feeding [50,51]. The relatively low integration of the skull may also signify that it has a modular organization, which has been previously observed using morphological, developmental and genetic lines of evidence [18,5256]. Numerous articulated bones and cartilages allow for a high level of cranial kinesis, while functional and biomechanical constraints put a pressure on its variability to preserve functional unity and stability [18,57].…”
Section: Discussionmentioning
confidence: 96%
“…These cranio-vertebral and hyo-pectoral interfaces lead to a more efficient suction mechanism and act as anchors to stabilize the head or to transfer power from the body during feeding [50,51]. The relatively low integration of the skull may also signify that it has a modular organization, which has been previously observed using morphological, developmental and genetic lines of evidence [18,5256]. Numerous articulated bones and cartilages allow for a high level of cranial kinesis, while functional and biomechanical constraints put a pressure on its variability to preserve functional unity and stability [18,57].…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that the loose association of jaw, suspensorium, and opercular elements in teleosts is a result of relaxed integration across the entire skull. A recently published study incorporating kinetic skull elements suggested that modularity may influence morphological divergence in complex feeding structures in labrid fishes (wrasses) (Larouche et al, 2022). Wrasses have evolved a diverse range of feeding strategies, which are likely to have been driven by the dietary diversity of their reef and shallow water habitats.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to structurally complex biodiverse settings like coral reefs (Roberts et al, 2002; Rabosky et al, 2018), it might seem environmentally homogenous, but the wide range of light levels, temperatures, currents, and food availability creates a surprising diversity of ecological niches that may drive adaptation. Most research on the phenotypic evolution of marine fishes focuses on clades (Larouche et al 2022; Evans et al 2022) or assemblages (Claverie and Wainwright, 2014) principally associated with shallow-water, coastal settings, often in proximity to reefs. However, recent surveys of fishes across marine habitats reveal that some settings are unexpected hotspots of phenotypic evolution (Friedman et al 2019; Martinez et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In his description of Polylepion , Gomon (1977) noted that, morphologically, the genus closely resembles Decodon , Pimelometopon , Semicossyphus , and Bodianus , the last a historically catch-all wrasse genus to which P. russelli was originally assigned (Gomon and Randall, 1975) and to which Semicossyphus (including Pimelometopon based on Gomon [1997]) was recently provisionally relegated (Santini et al, 2016). Molecular phylogenies of the Labridae revealed a sister-group relationship between Polylepion and Decodon (Aiello et al, 2017; Hughes et al, 2022; Larouche et al, 2022) and a paraphyletic Bodianus without the inclusion of Clepticus , Decodon , Polylepion , and Semicossyphus (Aiello et al, 2017) or without the inclusion of Clepticus and Semicossyphus (Hughes et al, 2022; Larouche et al, 2022). By combining the recently published time-calibrated phylogenomic tree for the Labridae (Hughes et al, 2022) with genetic sequences for over 300 species of wrasses (Aiello et al, 2017), we investigated the evolutionary history and timing of speciation events of the genus Polylepion , incorporating new genetic data for P. cruentum and the new species.…”
mentioning
confidence: 99%